Case report: Waldenstrom macroglobulinemia with systemic amyloidosis as the main manifestation - Yin, Junjing; Zhou, Xia; Yu, Shuyuan; Wu, Hongying; Zhong, Yuping (Frontiers in Medicine, 2024)
Systemic amyloidosis is a rare protein misfolding and deposition disorder leading to progressive organ failure. Waldenström macroglobulinemia (WM) with systemic amyloidosis as the main manifestation is even rarer. The patient presented with recurrent diarrhea and was not diagnosed in other hospitals for many times. Later, His diarrhoea worsened and was accompanied by sunken oedema of both lower limbs and dizziness. Renal biopsy showed deposits of PAS light-staining material in the glomeruli, interstitium, and small arteries, which stained positively with Congo red. Cardiac ultrasound showed interventricular septum thickening to 17 mm, right ventricular wall myocardial thickening of about 0.6 cm, and septal thickening of about 0.5 cm, considering myocardial amyloidosis. Electromyography showed abnormal peripheral nerve conduction. lymphoplasmacytic cells were found in the bone marrow. Taken together, he was diagnosed WM. He was treated with BR (Bendamustine + Rituximab) regimen. After 6 courses, the patient's discomfort was relieved and his weight gained 5Kg, and The level of serum IgM and dFLC decreased, and cardiac and renal assessments were more relieved. The patient has been followed up for more than 1 month.